Income, saving, and the theory of consumer behavior. - Duesenberry, James S. (Cambridge: Harvard University Press, 1949)
The document is a critique of the Keynesian consumption function. The paper further examines the problem associated with consumption function. "Under the title 'The consumption function t̓he original version of this book was submitted as a doctoral dissertation at the University of Michigan in February 1948."
Bibliography: p. [117]-124.
asm; 27/02/19
Loans
Keywords: Income; Consumption (Economics)